Arctic Sea Ice in a 1.5°C Warmer World. Issue 4 (20th February 2018) - Niederdrenk, Anne Laura; Notz, Dirk
Abstract: We examine the seasonal cycle of Arctic sea ice in scenarios with limited future global warming. To do so, we analyze two sets of observational records that cover the observational uncertainty of Arctic sea ice loss per degree of global warming. The observations are combined with 100 simulations of historical and future climate evolution from the Max Planck Institute Earth System Model Grand Ensemble. Based on the high‐sensitivity observations, we find that Arctic September sea ice is lost with low probability ( P ≈ 10%) for global warming of +1.5°C above preindustrial levels and with very high probability ( P > 99%) for global warming of +2°C above preindustrial levels. For the low‐sensitivity observations, September sea ice is extremely unlikely to disappear for +1.5°C warming ( P ≪ 1%) and has low likelihood ( P ≈ 10%) to disappear even for +2°C global warming. For March, both observational records suggest a loss of 15% to 20% of Arctic sea ice area for 1.5°C to 2°C global warming. Key Points: We find it is unlikely that September Arctic sea ice vanishes for 1.5°C global warming September sea ice might vanish for 2.0°C global warming, but observational uncertainty prevents a conclusive statement Internal variability causes a range of about ±0.2°C to the global warming magnitude at which September Arctic sea ice is lost